Structural Strength Finite Element Analysis for the Inscribed Cone Shaft of JD160A Traction Motor - LAN Wanli; KE Qirui (机车电传动)
By using ANSYS parameterized design language APDL, the entirely parameterized modeling of the rotor of traction motor was created, and the strength simulation of it was carried out under the rated work condition. On this basis, an analysis and a comparison were made regarding the influence of magnitude of interference, oil slot chamfer and coefficient of friction on the shaft’s equivalent stress, contact pressure and slippage in order to provide data reference for the fatigue failure of the cone shaft.